Consumo do iogurte caprino adicionado de farinha do cladódio de mandacaru (Cereus jamacaru DC.): efeitos sobre os parâmetros físicos, comportamentais e saúde intestinal de ratos - Dutra, Larissa Maria Gomes (2025)
The growing consumption of goat’s milk yogurt is driven by its various health benefits, including hypoallergenic properties and improved digestibility. Fermentation of goat’s milk not only enhances these characteristics but also increases its functional value by releasing bioactive compounds and beneficial fatty acids. Furthermore, goat yogurt represents an excellent matrix for the incorporation of potentially functional foods, such as mandacaru cladode (Cereus jamacaru). In this context, the present study aimed to investigate the effects of consuming goat’s milk yogurt supplemented with mandacaru cladode flour in young rats, encompassing physical, biochemical, behavioral parameters, and modulation of the intestinal microbiota. The animals were distributed into three groups: Goat Control Group (GC), which received distilled water; Goat Yogurt Group (YG), treated with goat yogurt; and Goat Yogurt with Mandacaru Group (YGM), which received goat yogurt supplemented with 7% mandacaru cladode flour. Physical and metabolic parameters were evaluated, including body weight, food intake, body fat percentage, and coronary and cardiovascular indices. Biochemical analyses included lipid profile, blood glucose, and hepatic enzymes. Serum metabolomic profiling was performed using proton nuclear magnetic resonance (^1H NMR). Hepatic and fecal cholesterol and triglycerides were also quantified, along with hepatic malondialdehyde levels. Anxiety-like behavior was assessed through the Elevated Plus Maze, Open Field, and Light–Dark Box tests. Additionally, cerebral oxidative stress markers, including malondialdehyde and carbonyl compounds, were measured. Finally, fecal microbiota composition was characterized. The results showed that the YGM group exhibited increased body weight, food intake, body fat, coronary and cardiovascular indices, lipid profile, and blood glucose compared to the GC and YG groups. NMR analysis indicated a tendency toward separation in methionine and leucine for the YG group compared to the YGM group, and in LDL and cholesterol for the YGM group compared to the GC group. Liver function revealed increased hepatic enzymes, cholesterol, and triglycerides in the YG and YGM groups, with possible non-alcoholic fatty liver disease observed, potentially associated with the high fatty acid content of yogurt, as well as increased hepatic oxidative stress in the YGM group. Regarding anxiety-like behavior, the YG and YGM groups spent more time in the open arms and the central area of the maze compared to the GC group, with the YGM group showing greater time and number of entries into the open arms than the YG group. Both groups displayed increased locomotion, rearing behavior, and reduced time in the corners of the open field, with greater ambulation in the YGM group. A reduction in cerebral oxidative stress markers was observed in both the YG and YGM groups. With respect to fecal microbiota analysis, the YGM group exhibited positive modulation, with increased microbial diversity and richness, highlighting the beneficial genera Blautia and Fusicatenibacter compared to the other groups. In conclusion, the consumption of goat’s milk yogurt enriched with mandacaru flour altered metabolic and hepatic parameters, inducing dyslipidemia, elevated blood glucose, and hepatic oxidative stress, while simultaneously promoting anxiolytic-like behavior and beneficial effects on the gut–brain axis in young rats. These findings indicate that, although this product may cause adverse metabolic alterations, it exerts anxiolytic effects and modulates fecal microbiota in rats.